Impactos do estresse ambiental na expressão de proteína Cry1F de milho Bt de primeira e segunda geração - Costa, Victor Hugo Duarte da (2019)
Bt corn plants expressing Cry proteins are grown in extensive areas with the aim of avoiding damage caused by lepidopteran pests in important agricultural production regions. The effectiveness of this technology is dependent mainly on the production of Bt proteins in adequate amounts that must be expressed in the different tissues of the plants that are targeted by the insects. On the other hand, Bt plantations are cultivated in heterogeneous environments with different environmental factors, such as water deficit, high temperatures, nutrient deficiency, among others. Such factors may directly interfere in the expression of insecticidal proteins and affect the efficacy of transgenic crops in pest control. The lower efficacy of the crops is reflected by the survival of the insects targets in the fields that are responsible for the reduction in productivity and may favor the evolution of the resistance of the target insects. Therefore, the objective of the thesis was to evaluate the behavior of Bt maize plants, which express Cry proteins under different environmental conditions, with different levels of irrigation and with environment with reduced nitrogen fertilization, both in the greenhouse and in the field. Different first and second generation Bt maize technologies, both Herculex® (Hx) and PowerCore® (Pw) technologies, both containing TC1507 technology plus its isogenic, nonbt corn, were constructed in the same genetic background and grown in different conditions with nitrogen reduction and different water conditions. The Cry1F content were quantified from the enzyme-linked immunosorbent assay (ELISA). In addition bioassays and analyzes of pest damage were performed to verify the protection of Bt crops. The reduction of nitrogen fertilization coupled with exposure for no irrigation periods and different water regimes both in the greenhouse and in the field did not reduce the content of Cry1F proteins nor did they impair the effectiveness of the control of S. frugiperda for both plants first (Hx) and second generation (Pw) in the experimental conditions used. In addition, no significant differences in Bt-related productivity was observed on field analyzes.